2023
DOI: 10.3390/life13010225
|View full text |Cite
|
Sign up to set email alerts
|

Metastasis of Hepatocellular Carcinoma in the Pouch of Douglas Successfully Treated by Radiation Therapy: A Case Report

Abstract: Metastasis of hepatocellular carcinoma (HCC) in the pouch of Douglas is relatively rare. A 65-year-old man with liver cirrhosis was admitted for detailed examination of a pelvic tumor. He had a previous history of ruptured HCC, and received emergent hemostasis with transcatheter arterial embolization followed by curative ablation. His blood tests showed an increase in des-gamma-carboxy prothrombin (DCP). Contrast-enhanced computed tomography (CE-CT) revealed a heterogeneously enhanced large pelvic tumor, but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…A recent case report from Japan also supports radiotherapy as a viable strategy for treating peritoneal seeding masses of HCC. 19 In addition, recent advances in systemic therapy for HCC might play a key role in managing peritoneal metastasis. A recent case report from Japan suggested that peritoneal recurrence after surgical resection was effectively treated with first-line lenvatinib, second-line sorafenib, and third-line atezolizumab in addition to bevacizumab combination therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent case report from Japan also supports radiotherapy as a viable strategy for treating peritoneal seeding masses of HCC. 19 In addition, recent advances in systemic therapy for HCC might play a key role in managing peritoneal metastasis. A recent case report from Japan suggested that peritoneal recurrence after surgical resection was effectively treated with first-line lenvatinib, second-line sorafenib, and third-line atezolizumab in addition to bevacizumab combination therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A recent case report from Japan also supports radiotherapy as a viable strategy for treating peritoneal seeding masses of HCC. 19 …”
Section: Discussionmentioning
confidence: 99%